Have You Any Wool? : The Creative Use of Yarn - Messent, Jan (London Search Press, 1993)
This book contains hundreds of witty and creative ways of using up oddments of yarn. Explore your own design potential by combining basic knitting and crochet skills to create decorative projects.
Include Index, Glossary and Illustration
Keywords: Crocheting -- Knitting -- Wool